Indonesia’s Nurcholish Madjid and Abdurrahman Wahid as Intellectual ‘Ulamā’: The Meeting of Islamic Traditionalism and Modernism in neo-Modernist Thought - Greg Barton (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
Indonesian Islamic discourse of the modern record Nurcholish Madjid and Abdurrahman Wahid as the two main characters for the development of a reform movement known as neo-modernism movement. The question that should be asked is: why neo-Modernist Islamic thought this was so a place among Indonesian Muslims?DOI: 10.15408/sdi.v4i1.786